2021
DOI: 10.3390/jcm10050926
|View full text |Cite
|
Sign up to set email alerts
|

Age and Overweight Are Not Contraindications for a Breast Reconstruction with a TMG-Flap—A Risk and Complication Analysis of a Retrospective Double Center Study Including 300 Patients

Abstract: Introduction: The transverse myocutaneous gracilis (TMG) flap has become a popular and reliable alternative for autologous breast reconstruction. Initially described as a valuable tissue source for women with low body-mass index, indications nowadays have widely expanded. The Western civilization demographic development with its aging population and the steady growing average BMI has led to increasing breast reconstructions with TMG flaps in overweight and aged individuals. Patients and Methods: A total of 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The exact numbers regarding the indication of secondary surgeries including lipofilling are highly variable and depend on multiple factors though such as patient satisfaction, demand, and the individual local health care provider. A recent study demonstrated that increased age and overweight are no contraindications to breast reconstructions with the TMG flap and did not cause any increase of complications [35].…”
Section: Discussionmentioning
confidence: 99%
“…The exact numbers regarding the indication of secondary surgeries including lipofilling are highly variable and depend on multiple factors though such as patient satisfaction, demand, and the individual local health care provider. A recent study demonstrated that increased age and overweight are no contraindications to breast reconstructions with the TMG flap and did not cause any increase of complications [35].…”
Section: Discussionmentioning
confidence: 99%
“…The safety and applicability of the TMG flap have been outlined in plenty of studies [5,8,16,17]. The TMG flap is based on the dominant pedicle to the gracilis muscle and its perforators nourishing the excess of fat and skin laxity harvested from the medial thigh [18].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative Doppler probe examination eases the precise localization of the dominant pedicle and may shorten the flap harvest and operation time. Recently, Schwaiger et al reported on the safe use of the TMG flap for breast reconstruction in patient populations with BMI > 25 kg/m 2 expanding its applications for breast reconstruction [17]. Moreover, Weitgasser et al conducted the first head-to-head comparison of double DIEP flaps and double TMG flaps for simultaneous breast reconstruction, emphasizing the rising value of the TMG flap for bilateral breast reconstruction [19].…”
Section: Discussionmentioning
confidence: 99%
“…Since its first description by Yousif et al, the transverse myocutaneous gracilis (TMG) flap has become a commonly used free flap for breast reconstruction due to its versatility, constant and reliable anatomy and relatively simple flap harvest [ 26 ]. Although the DIEP flap remains to be the gold standard in autologous breast reconstruction for most plastic surgeons, the availability and reliability of the TMG flap in patients with a low BMI who do not offer enough tissue for an abdominal based reconstruction make the TMG flap a sound second choice for breast reconstruction in such patients [ 27 ]. Donor site morbidity of the thigh has been postulated as a drawback but has been shown to be comparable to abdominal based and other free flap options available [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also included cases of female Poland syndrome patients who received breast reconstructions with TMG flaps. Since the TMG flap is usually considered a smaller sized flap in breast reconstruction with an average weight of 320 g, the average BMI for optimal treatment should be <25 kg/m 2 , although higher BMI is not a contraindication to utilization of the TMG flap [ 27 , 32 ]. However, in patients with a higher body weight, the DIEP flap which offers a mean average weight of 550 g is frequently a better choice for reconstruction since it offers more volume and many patients potentially benefit from the donor site in the form of an abdominoplasty [ 33 ].…”
Section: Discussionmentioning
confidence: 99%